Perineal urethrostomy in the cat. Technique and complications - PAPAZOGLOU (Λ.Γ. ΠΑΠΑΖΟΓΛΟΥ), L. G.; BASDANI (Ε. ΜΠΑΣΔΑΝΗ), E. (Journal of the Hellenic Veterinary Medical Society, 2017)
Perineal urethrostomy (PU) is the surgical procedure performed in the male cat in order to create a permanent stoma of the pelvic urethra to the skin of the perineal region. The first urehrostomy was devised on early sixties and since then many urethrostomy techniques were invented. On 1971 Wilson and Harrison invented a technique of PU that is currently used by the majority of surgeons, because of the better results and fewer complications compared to the other urethrostomy techniques. Indications for performing PU in the male cat include recurrent urethral obstruction associated with lower urinary tract disease, as an emergency procedure for the restoration of the patency of the obstructed urethra when all other conservative measures failed, priapism, strictures, trauma and urethral neoplasms. For a successful PU: 1) the pelvic urethra should be incised and anastomosed in the perineum cranial to the bulbourethral glands, 2) the urethra should be completely freed from its attachments to the ishium so as to decrease tension to the stoma, and 3) accurate apposition of the urethra to the skin should be performed to achieve first intention healing of the stoma site and avoid stricture formation. Complications following PU may include urethral stricture, ascending urinary tract infection, haemorrhage, subcutaneous urine extravasation resulting in sloughing and dehiscence of the stoma, skin fold dermatitis, urinary and fecal incontinence, bladder atony, iatrogenic perineal hernia and rectourethral fistula. Prepubic, subpubic or transpelvic urethrostomy may be used to salvage postoperative urethral stricture. Pepubic urethrostomy is the only salvage technique that has been evaluated long-term, but is associated with serious complications such as urine scalding, urinary incontinence and urinary tract infection. Perineal urethrostomy aims at relieving urethral obstruction and is part of the medical management of cats with recurrent or persistent urethral plug formation.